Andrew Carnegie and the age of steel - History Channel (Television network); A & E Home Video (Firm); New Video Group (New York : A & E Home Video : Distributed in the U.S. by New Video Group, 2005)
Examines the development of the steel industry and the part Andrew Carnegie played in it.
DVD, region 1; Dolby stereo.
Title from container.
Originally broadcast on the History Channel in 1997.
MPAA rating: Not rated.
Keywords: Carnegie, Andrew, -- 1835-1919.; Steel industry and trade -- United States; Steel; Iron and steel workers -- United States; Philanthropists -- United States -- Biography; Industrialists -- United States -- Biography